Exploring TNFR1: from discovery to targeted therapy development - Yingying Li; Ruiwei Ye; Haorui Dai; Jiayi Lin; Yue Cheng; Yonghong Zhou; Yiming Lu (Journal of Translational Medicine)
Abstract This review seeks to elucidate the therapeutic potential of tumor necrosis factor receptor 1 (TNFR1) and enhance our comprehension of its role in disease mechanisms. As a critical cell-surface receptor, TNFR1 regulates key signaling pathways, such as nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPK), which are associated with pro-inflammatory responses and cell death. The intricate regulatory mechanisms of TNFR1 signaling and its involvement in various diseases, including inflammatory disorders, infectious diseases, cancer, and metabolic syndromes, have attracted increasing scholarly attention. Given the potential risks associated with targeting tumor necrosis factor-alpha (TNF-α), selective inhibition of the TNFR1 signaling pathway has been proposed as a promising strategy to reduce side effects and enhance therapeutic efficacy. This review emphasizes the emerging field of targeted therapies aimed at selectively modulating TNFR1 activity, identifying promising therapeutic strategies that exploit TNFR1 as a drug target through an evaluation of current clinical trials and preclinical studies. In conclusion, this study contributes novel insights into the biological functions of TNFR1 and presents potential therapeutic strategies for clinical application, thereby having substantial scientific and clinical significance.